Penanaman Embrio Pada Rahim Istri yang Lain (Analsis Kritis Terhadap Fatwa MUI Tentang Kehamilan Berbantu) - Najib Junaidi - (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2019)
This paper discusses of the MUI fatwa on June 13, 1979, about the practice of in vitro fertilization usinganother wife's womb. This practice was declared haram by the Indonesian Ulama Council's fatwa on the 13June 1979 about in vitro fertilization / Artificial Insemination. The MUI Fatwa normative argument, it willcause complications in inheritance issues, especially between children born with mothers who have ovum andmothers who conceive and give birth, and vice versa. This research is a normative juridical study, with theapproach of ushul fiqh, qawa'id fiqhiyah and comparison (comparison). The results showed that the practice of invitro fertilization by using another wife's womb, the law is permissible. Children born through this process have abearing for surrogate mothers who have conceived and delivered them. The complexity of inheritance issues that arefeared in the MUI fatwa can be overcome by determining the relationship of the nasab, because the nasabrelationship is one of the causes of inheritance. The mother of the owner of the ovum who becomes the origin or thesurrogate mother can be positioned the same as the mother who must be respected by the child, but has noinheritance relationship.